2022
DOI: 10.3389/fcimb.2022.997018
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis in nonalcoholic fatty liver disease: pathogenesis, diagnosis, and therapeutic implications

Abstract: The incidence of nonalcoholic fatty liver disease (NAFLD) is increasing recently and has become one of the most common clinical liver diseases. Since the pathogenesis of NAFLD has not been completely elucidated, few effective therapeutic drugs are available. As the “second genome” of human body, gut microbiota plays an important role in the digestion, absorption and metabolism of food and drugs. Gut microbiota can act as an important driver to advance the occurrence and development of NAFLD, and to accelerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 128 publications
0
34
0
Order By: Relevance
“…As a result, the intestinal microbiota has become a non-invasive biomarker for diagnosing and evaluating NAFLD ( Fianchi et al, 2021 ). Antibiotic treatment and stool transplantation are emerging as new strategies for preventing and treating NAFLD ( Fang et al, 2022 ). Modifying the microbiota has been identified as a potential therapeutic approach for NAFLD by modulating the activation of KCs.…”
Section: Activation Of Kcsmentioning
confidence: 99%
“…As a result, the intestinal microbiota has become a non-invasive biomarker for diagnosing and evaluating NAFLD ( Fianchi et al, 2021 ). Antibiotic treatment and stool transplantation are emerging as new strategies for preventing and treating NAFLD ( Fang et al, 2022 ). Modifying the microbiota has been identified as a potential therapeutic approach for NAFLD by modulating the activation of KCs.…”
Section: Activation Of Kcsmentioning
confidence: 99%
“…This microbiome may be characteristic of the population due to dietary and hygiene acts of the host, but it also presents a composition that is almost specific to each individual. Recent studies have shown the importance of the individual’s microbiome in the origin and/or intensity of different metabolic disorders, such as liver cirrhosis and hepatocarcinomas [ 304 ], progression of neurodegenerative diseases [ 304 , 305 ], glycolipids metabolism disorders [ 306 ], obesity [ 307 ], myocardinal fibrosis and some cardiovascular diseases [ 308 ], arterial hypertension [ 307 ], among others. These are consequences of the so-called gut dysbiosis, or dysbacteriosis, caused by an imbalance in the composition of the microbiome, altering its metabolic activity as a whole [ 202 , 309 , 310 ].…”
Section: Microbiome and Faecal Transplant: The Futurementioning
confidence: 99%
“…16 Recently, the role of gut microbiota and microbial metabolites in NAFLD has attracted more attention, as there seems to be significant dysbiosis-related production of ethanol to induce steatosis and inflammation in the liver of some individuals with NAFLD. 17 Against this background, some suggest that gut dysbiosis may be a causal factor in the pathogenesis and progression of NAFLD 18 -perhaps even more so in individuals without classic risk factors of the metabolic syndrome. 19 Antibiotics are known to cause significant short-term and, to some extent, even long-term taxonomic changes in gut microbiota that may impact the natural history of several diseases.…”
Section: Introductionmentioning
confidence: 99%